The Concept of Tri Hita Karana in Kakawin Siwaratrikalpa as a Means to Interpret Life - Suminto, Suminto; Kustiyanti, Dyah (Institut Seni Indonesia Denpasar, 2023)
Old Javanese literature, especially Kakawin Siwaratrikalpa, has an essential role among the Hindu community in Bali, not only because of its captivating story elements but also because it is essential for human life as it contains artistic values, religious values, moral teachings (ethics), manners, character education, philosophy, law, and morals. Tri Hita Karana is a concept of balancing the relationship between humans and God, humans and others, and humans and their natural environment to achieve prosperity and harmony in life in the world. Human life has undergone significant changes due to the changing times. The demands of modern life have brought human behavior to problems that need attention. The advancement of science and technology has caused a shift in social values, which has led humans to promiscuity, moral decline, the conflict between religious communities, lifestyle changes, environmental degradation, exploitation of natural resources, and even environmental destruction. This research is qualitative descriptive research by applying the concept of Tri Hita Karana. The source of the data is scientific, meaning that apart from observing texts, researchers are trying to observe and understand empirical phenomena directly in people's lives. The theory used is the theory of Human Relations. The results of the discussion prove that the three parts of the Tri Hita Karana concept are always related and cannot be separated. Humans, as the main actors in life, must continue to seek and strive for a safe, peaceful, and happy life.